2020
DOI: 10.1111/epi.16784
|View full text |Cite
|
Sign up to set email alerts
|

FBXO28 causes developmental and epileptic encephalopathy with profound intellectual disability

Abstract: Chromosome 1q41‐q42 deletion syndrome is a rare cause of intellectual disability, seizures, dysmorphology, and multiple anomalies. Two genes in the 1q41‐q42 microdeletion, WDR26 and FBXO28, have been implicated in monogenic disease. Patients with WDR26 encephalopathy overlap clinically with those with 1q41‐q42 deletion syndrome, whereas only one patient with FBXO28 encephalopathy has been described. Seizures are a prominent feature of 1q41‐q42 deletion syndrome; therefore, we hypothesized that pathogenic FBXO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The majority of Tier 1 epilepsy genes (126/143) were also found in at least one of the four assessed gene panels. Those 17 high-confidence genes not included in the assessed panels include genes both gene associated with somatic variants (e.g., BRAF [24]) and genes that should be added to gene panels (e.g., FBXO28 [25] or KCNC2 [26]). When comparing our comprehensive Tier 2 gene list of 738 genes with (caption on next page) the gene panel genes, we found that almost 50% of those genes (n = 365) are included in at least one of the gene panels.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of Tier 1 epilepsy genes (126/143) were also found in at least one of the four assessed gene panels. Those 17 high-confidence genes not included in the assessed panels include genes both gene associated with somatic variants (e.g., BRAF [24]) and genes that should be added to gene panels (e.g., FBXO28 [25] or KCNC2 [26]). When comparing our comprehensive Tier 2 gene list of 738 genes with (caption on next page) the gene panel genes, we found that almost 50% of those genes (n = 365) are included in at least one of the gene panels.…”
Section: Resultsmentioning
confidence: 99%
“…All three patients with variants in WDR26/FBXO28 were affected by severe ID, epilepsy, dysmorphia, behavioral abnormalities, and central nervous system alterations, including incomplete hippocampal inversion, corpus callosum hypoplasia, or cerebellar atrophy. None of our patients showed the characteristic multi-system features of patients affected by 1q41-q42 deletion syndrome [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, evidence has implied that FBXO28 may be involved in the occurrence and development of multiple human diseases. For example, FBXO28 variants cause developmental and epileptic encephalopathy, and with severe intellectual disability [ 31 ]. It has been found that FBXO28 is needed for the normal mitosis and affects the cell cycle by regulating topoisomerase IIα activity to maintain genome stability [ 32 ].…”
Section: Discussionmentioning
confidence: 99%